Impact of switching to infliximab biosimilars on treatment patterns among US veterans receiving innovator infliximab. (3rd April 2022) - Lin, Iris; Melsheimer, Richard; Bhak, Rachel H.; Lefebvre, Patrick; DerSarkissian, Maral; Emond, Bruno; Lax, Angela; Nguyen, Catherine; Wu, Melody; Young-Xu, Yinong
Abstract: Objective: To compare treatment patterns of United States (US) veterans stable on innovator infliximab (IFX) who switched to an IFX biosimilar (switchers) or remained on innovator IFX (continuers). Methods: US Veterans Healthcare Administration data (01/2012–12/2019) were used to identify adults with rheumatoid arthritis (RA), psoriatic arthritis (PsA), plaque psoriasis (PsO), ankylosing spondylitis (AS), or Crohn's disease and ulcerative colitis (i.e. inflammatory bowel disease [IBD]), treated with innovator or biosimilar IFX. Index date was the first IFX biosimilar administration for switchers or a random innovator IFX administration for continuers. Patients were required to have ≥5 innovator IFX administrations during the 12 months pre-index (prevalent population). Patients with ≥12 months of observation prior to the first innovator IFX administration were analyzed as the primary population (incident population), and data were assessed from start of innovator IFX. Inverse probability of treatment weighting was used to balance baseline characteristics between cohorts. Treatment patterns were evaluated post-index; continuers were censored before switching to IFX biosimilar. Discontinuation was defined as switching to another biologic (including innovator IFX) or having ≥120 days between 2 consecutive index treatment records. Results: In the incident population, mean [median] duration of follow-up was 737 [796] days among switchers ( N  = 838) and 479 [337] days among continuers ( N  = 849). Compared to continuers, switchers were 2.88-times more likely to discontinue index therapy (hazard ratio [HR] = 2.88, p  < .001) and 4.99-times more likely to switch to another innovator biologic (HR = 4.99, p  < .001). Of 653 switchers switching to another innovator biologic, 594 (91.0%) switched back to innovator IFX. Results were similar among the prevalent population and RA and IBD subgroups. Conclusion: Patients switching from innovator to biosimilar IFX were more likely to discontinue treatment and switch to another innovator biologic (notably back to innovator IFX) than those remaining on innovator IFX; however, reasons for discontinuation and switching are unknown.